2010
DOI: 10.1002/tox.20646
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin induces apoptosis in SCC‐4 human tongue cancer cells through mitochondria‐dependent and ‐independent pathways

Abstract: Although there have been advances in the fields of surgery, radiotherapy, and chemotherapy of tongue cancer, the cure rates are still not substantially satisfactory. Capsaicin (trans‐8‐methyl‐N‐vanillyl‐6‐nonenamide) is the major pungent ingredient of hot chili pepper and has been reported to have an antitumor effect on many human cancer cell types. The molecular mechanisms of the antitumor effect of capsaicin are not yet completely understood. Herein, we investigated whether capsaicin induces apoptosis in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Cap has been previously demonstrated to inhibit the proliferation of, or induce apoptosis in, numerous varieties of human cancer, including lung, prostate, pancreatic and breast cancer, in vitro and in vivo (912). Cap causes tumor cell cycle arrest in S or G 1 /G 0 phase in NPC-TW 039 human nasopharyngeal carcinoma cells, MCF-7 human breast cells, BT-474 cells, SKBR-3 cells, MDA-MB231 cells and SCC-4 human tongue cells, in model systems in vitro and in vivo (1315). Furthermore, Cap triggers apoptosis in >40 distinct tumor cell lines, primarily through the mitochondrial pathway or death receptor pathway (16).…”
Section: Introductionmentioning
confidence: 99%
“…Cap has been previously demonstrated to inhibit the proliferation of, or induce apoptosis in, numerous varieties of human cancer, including lung, prostate, pancreatic and breast cancer, in vitro and in vivo (912). Cap causes tumor cell cycle arrest in S or G 1 /G 0 phase in NPC-TW 039 human nasopharyngeal carcinoma cells, MCF-7 human breast cells, BT-474 cells, SKBR-3 cells, MDA-MB231 cells and SCC-4 human tongue cells, in model systems in vitro and in vivo (1315). Furthermore, Cap triggers apoptosis in >40 distinct tumor cell lines, primarily through the mitochondrial pathway or death receptor pathway (16).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, research studies have demonstrated the applications of capsaicin as a specific and potent anti-carcinogenic agent through the apoptosis pathway in both in vitro and in vivo cancer models, whereas it does not induce cytotoxicity in normal cells [3], [4], [5], [6], [7]. The mechanisms underlying capsaicin-induced apoptosis may involve multiple signaling pathways and depend upon cell types [3], [8]. Capsaicin acts as the high affinity agonist that directly binds to the transient receptor potential vanilloid subtype 1 (TRPV1) and TRPV6 receptors that belong to the transient receptor potential (TRP) superfamily of nonselective cation-channels.…”
Section: Introductionmentioning
confidence: 99%
“…Capsaicin acts as the high affinity agonist that directly binds to the transient receptor potential vanilloid subtype 1 (TRPV1) and TRPV6 receptors that belong to the transient receptor potential (TRP) superfamily of nonselective cation-channels. They are overexpressed mainly in human cancer cells compared to normal cells [4], [5], [8], [9], [10], [11], including HepG2 cells [12]. The binding of capsaicin to TRPV1 induces apoptosis via multiple mechanisms, including the generation of reactive oxygen species (ROS), such as superoxide radicals and hydrogen peroxide as well as impairment of ER calcium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that death-receptor, mitochondria and endoplasmic reticulum played an important role in apoptosis (8,9). The activation of effector caspases such as caspase-3 and -7 by initiator caspases (caspase-8 and -9) are responsible for the cleavage of cellular substrates degrading the chromosomes into nucleosomal fragments during apoptosis (10,11). Two major pathways are involved in cell apoptosis; the death receptor pathway and the mitochondria-dependent pathway.…”
Section: Introductionmentioning
confidence: 99%